The Role of Food Security Policy and Educational Management in Reducing Stunting Among Children - Pitri, Sari Ramayeni; Yusran, Rahmadani (Journal of Educational Management Research, 2025)
This study examines the implementation of food security policies in stunting prevention program, through the lens of Grindle’s (1980) policy implementation framework. Using a descriptive qualitative approach, data were gathered via in-depth interviews, observations, and document analysis involving government officials, village institutions, and beneficiary communities. The analysis identifies four key barriers: limited community participation, inadequate financial and human resources, inequitable and elite-centered aid distribution, and geographical as well as climatic constraints. These findings reveal a significant gap between policy content and implementation context, where participatory and sustainability principles mandated by national and regional frameworks have not been effectively realized at the local level. Theoretically, the study extends Grindle’s model by incorporating ecological and spatial dimensions as critical factors shaping policy outcomes. Practically, it underscores the importance of adaptive policy design that integrates local geographic and socio-cultural contexts, fosters community engagement, enhances inter-sectoral coordination, and promotes participatory budgeting at the village (nagari) level to strengthen food security and reduce stunting sustainably.